AN INNOVATIVE IMPLEMENTATION, DESIGN AND ANALYSIS OF SMART HEALTHCARE MONITORING ARCHITECTURE USING IOT AND BLOCKCHAIN TECHNOLOGY - Reddy, P. Satish; Kashyap, Meenakshi; Mohapatra, Shubhalaxmi; Aleria, Dinesh; Mondal, Somnath; Bhattacharyya, Suman Kumar; Mishra, Sandeep; Shukla, Kaustubh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The combination of Internet of Things (IoT) and blockchain technology is a promising paradigm to enhance healthcare monitoring systems. These technologies together enable data to be collected, transmitted and stored in real time in a secure and transparent way, addressing a number of key challenges in contemporary healthcare including data privacy, security, interoperability and efficiency. In this paper, a complete architecture for IoT and blockchain based smart healthcare monitoring system has been proposed. The architecture uses IoT to collect and monitor patient data and blockchain to guarantee the integrity, privacy and traceability of medical records. The paper presents the design considerations, system components, communication protocols and security mechanisms. We have designed and evaluated a prototype to demonstrate the feasibility and effectiveness of the approach proposed. The results show that the proposed architecture can improve the reliability, security and scalability of healthcare monitoring systems remarkably.